Feasibility of self-collection of fecal specimens by randomly sampled women for health-related studies of the gut microbiome - Feigelson, Heather Spencer (BioMed Central, 2014)
BACKGROUND: The field of microbiome research is growing rapidly. We developed a method for self-collection of fecal specimens that can be used in population-based studies of the gut microbiome. We conducted a pilot study to test the feasibility of our methods among a random sample of healthy, postmenopausal women who are members of Kaiser Permanente Colorado (KPCO). We aimed to collect questionnaire data, fecal and urine specimens from 60 women, aged 55–69, who recently had a normal screening mammogram. We designed the study such that all questionnaire data and specimens could be collected at home. RESULTS: We mailed an invitation packet, consent form and opt-out postcard to 300 women, then recruited by telephone women who did not opt-out. Verbally consented women were mailed an enrollment package including a risk factor questionnaire, link to an online diet questionnaire, specimen collection kit, and instructions for collecting stool and urine. Specimens were shipped overnight to the biorepository. Of the 300 women mailed an invitation packet, 58 (19%) returned the opt-out postcard. Up to 3 attempts were made to telephone the remaining women, of whom 130 (43%) could not be contacted, 23 (8%) refused, and 12 (4%) were ineligible. Enrollment packages were mailed to 77 women, of whom 59 returned the risk factor questionnaire and specimens. We found no statistically significant differences between enrolled women and those who refused participation or could not be contacted. CONCLUSIONS: We demonstrated that a representative sample of women can be successfully recruited for a gut microbiome study; however, significant personal contact and carefully timed follow-up from the study personnel are required. The methods employed by our study could successfully be applied to analytic studies of a wide range of clinical conditions that have been postulated to be influenced by the gut microbial population.